Factors Favoring Greece's Inward Foreign Direct Investment in the Aftermath of the Global Financial Crisis: An Exploratory Survey. Issue 3 (3rd July 2019) - Vlachos, Vasileios A.; Mitrakos, Panagiotis; Tsimpida, Chrysanthi; Tsitouras, Antonis; Bitzenis, Aristidis
Abstract: Greece has suffered the worst from the late 2000s global financial crisis. Despite the completion of the economic adjustment program the rate of recovery in Greece is still weak. The liquidity constraints in the Greek economy imply that the investment shock, which will accelerate its recovery rate, will be an outcome of investment inflows by privatizations and/or other opportunities arising to foreign investors (inward FDI) due to the devaluation of the assets in Greece caused by the crisis. However, the level of attracted by the Greek economy has always been well below the European Union average. This paper investigates the factors favoring inward FDI in Greece after the crisis. A survey is made by the use of a questionnaire for the collection of primary data on the activity of multinationals in Greece and non-parametric methods are used for investigating the attractiveness of the Greek market and the decision to invest.